Valuation Implications of Reliability Differences: The Case of Nonpension Postretirement Obligations - Byeonghee (Ben) Choi; Collins, Daniel W.; Johnson, W. Bruce (The Accounting Review, 1997)
[This paper examines whether accumulated postretirement benefit obligations (APBO) are useful in assessing equity market values. Using an extension of the econometric procedures outlined in Barth (1991), we use observed market capitalization rates on accounting measures to estimate "noise ratios" defined as the ratio of measurement error variance to the total variance of the accounting measure. Differences in estimated noise ratios are then used to make inferences about the relative reliability of APBO and pension liability measures. We find that APBO amounts are marginally significant in explaining cross-sectional differences in equity values, but are capitalized at a much lower rate than pension obligations. Consistent with predicted differences in reliability, the estimated noise ratio for APBO is significantly greater than that for pension obligations. Moreover, we find estimated APBO noise ratios vary predictably across firms as a function of the retiree/active employee ratio and the likelihood of health care benefit reductions.]